Influence of iron mass on Cr isotope fractionation associated with Cr(VI) reduction by zero-valent iron - Filip Budimir; Richard T. Amos; Carol J. Ptacek; David W. Blowes (Journal of Contaminant Hydrology, 2026)

Estimation of Recommended Damping Coefficient Range to Achieve Target Peak Knee Flexion in a Passive Prosthetic Knee - Nina T. Petelina; V. N. Murthy Arelekatti; Amanda L. Shorter; W. Brett Johnson; Jenny A. Kent; John T. Brinkmann; Matthew J. Major; Amos G. Winter, V (Annals of Biomedical Engineering, 2026)

Phylogeographic perspectives on conserving the endangered monotypic genus Acanthochlamys (Velloziaceae) - Dennis A. Wakhungu; Zhi-Peng Li; Amos Kipkoech; Moses C. Wambulwa; Oyetola O. Oyebanji; Richard I. Milne; Christopher Dudley; Winnie W. Mambo; Bo Xu; Jie Liu (Conservation Genetics Resources, 2026)

Comparing tree swallow dispersal strategies in a continuous mainland environment - Kelly K. Hallinger; Teresa M. Pegan; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; David Chang van Oordt; Valentina Ferretti; Anna M. Forsman; Jennifer R. Gaul; Paulo E. Llambías; Sophia C. Orzechowski; J. Ryan Shipley; et al. (Ecology, 2026)
Dispersal is one of the most important aspects of animal behavior and can have far‐reaching consequences for organismal ecology and evolution. Despite recent theoretical advances in understanding why individuals within the same population vary in dispersal behavior, relatively few studies have empirically evaluated the long‐term causes and consequences of variable dispersal within natural populations. In this study, we used life history data collected over the course of 16 years to examine fitness outcomes in 867 known‐age female tree swallows breeding in New York, USA, that differed in their dispersal status: “immigrant” females, defined as dispersers that hatched elsewhere, and “local” females, defined as non‐dispersers that hatched within the study site and returned there after migration to breed. We also compared the life history responses of immigrant and local females to natural variation in weather, nest predation risk, and social environment at their breeding site. Local females were more likely to produce fledglings that recruited into the study area as adults. We also found several instances in which dispersal status interacted with an environmental metric to influence relative fitness, and these responses were largely consistent across life history measures. Overall, immigrant females were relatively resilient to variation in their extrinsic environment, while local females were highly sensitive to environmental conditions at the breeding site, performing relatively well when conditions were benign and faring relatively poorly as conditions became more stressful. We found little evidence that distance dispersed within a study site impacted female fitness, suggesting that the dispersal‐associated differences in fitness that we observed operate mostly across broader spatial scales. Future work should undertake the direct and simultaneous measurement of behavior, physiology, and fitness of immigrant and local females across environmental contexts and should seek to understand whether and how context‐dependent fitness variation of dispersers and non‐dispersers scales up to influence larger ecological and evolutionary processes.

Comminution environment-defined collector adsorption behaviour of copper sulphide ore - T. Amos Judge; G. Abaka-Wood; C. Greet; W. Skinner; R. Asamoah (Minerals Engineering, 2025)

A novel method for detecting per- and polyfluoroalkyl substances (PFAS) by colorimetric emulsion extraction - W. Cary Hill; Charles K. Mack; Tyler W. Seguine; Thomas M. Amos; Mark L. Ballentine; Alan J. Kennedy (Chemosphere, 2025)

Diavik Waste Rock Project: Post-emplacement investigation of sulfide weathering from a deconstructed experimental waste-rock pile - Colleen Atherton; David Wilson; Steven P. Holland; Katherine E. Raymond; David R. Barsi; Jordan Zak; Leslie Smith; David C. Sego; Richard T. Amos; Dogan Paktunc; Carol J. Ptacek; David W. Blowes (Applied Geochemistry, 2025)

Random Mating in a Hybrid Zone Between Two Putative Climate‐Adapted Bird Lineages With Predicted Mitonuclear Incompatibilities - Lana M. Austin; J. Nevil Amos; Diana A. Robledo‐Ruiz; Jessica W. Zhou; Rohan H. Clarke; Alexandra Pavlova; Paul Sunnucks (Molecular Ecology, 2025)
Biochemical and evolutionary interactions between mitochondrial and nuclear genomes (‘mitonuclear interactions’) are proposed to underpin fundamental aspects of biology including evolution of sexual reproduction, adaptation and speciation. We investigated the role of pre‐mating isolation in maintaining functional mitonuclear interactions in wild populations bearing diverged, putatively co‐adapted mitonuclear genotypes. Two lineages of eastern yellow robin Eopsaltria australis —putatively climate‐adapted to ‘inland’ and ‘coastal’ climates—differ by ~7% of mitogenome nucleotides, whereas nuclear genome differences are concentrated into a sex‐linked region enriched with mitochondrial functions. Female‐specific selection and male‐mediated gene flow across the hybrid zone where the lineages coexist and interbreed can explain this pattern. It remains unknown whether lineage divergence is driven by intrinsic incompatibilities (particularly in females; Haldane's rule), extrinsic selection, both, or other drivers. We tested whether lineage divergence could be facilitated by non‐random mate‐pairing with respect to partners' mitolineage and/or mitonuclear genes encoded by the Z sex‐chromosome, which differ between the lineages. We used field‐, Z‐linked‐ and mitolineage data from two locations where lineages hybridise to test whether females mate disproportionately with (1) males of their own mitolineage and/or bearing similar Z‐linked variation, as might be expected if hybrids experience intrinsic incompatibilities, or (2) putatively locally‐adapted males, as might be expected under environmental selection. Comparing field observations with simulations provided no evidence of non‐random mating, thus drivers of observed population genetic patterns are consistent with reduced female gene flow likely acting post‐mating. Future tests of female‐biased mortality at different life stages and habitat selection may clarify mechanisms of selection.

Chromium isotope fractionation during the removal of hexavalent chromium by oak-based biochar - Filip Budimir; Carol J. Ptacek; Richard T. Amos; David W. Blowes (Chemosphere, 2024)

Preparation, characterization, and applications of kaolin/kaolin-based composite membranes in oily wastewater treatment: Recent developments, challenges, and opportunities - Amos K. Avornyo; Shadi W. Hasan; Fawzi Banat; Constantinos V. Chrysikopoulos (Journal of Environmental Management, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Integrating both restoration and regeneration potentials into real-world forest restoration planning: A case study of Hong Kong - He Zhang; Calvin K.F. Lee; Ying Ki Law; Aland H.Y. Chan; Jinlong Zhang; Stephan W. Gale; Alice Hughes; Martha J. Ledger; Man Sing Wong; Amos P.K. Tai; Billy C.H. Hau; Jin Wu (Journal of Environmental Management, 2024)

Participant Evaluation of a Multi-disciplinary Oncology Preceptorship Training Program for Oncology Health Professionals from Kumasi, Ghana - Kenneth W. Merrell; Thomas Okpoti Konney; Osei Acheamfour; Joseph Lucido; Abena Yeboah Aduse-Poku; Amanika Kumar; Mavis Bobie Ansah; Adu Tutu Amankwa; Dean Shumway; Fred Kwame Awittor; Augustina Badu-Peprah; Lionel Aurelien A. Kankeu Fonkoua; et al. (Journal of Cancer Education, 2024)
A critical shortage of skilled healthcare workers is a primary cause of disparate global cancer outcomes. We report participant evaluation of a multidisciplinary preceptorship program. In collaboration with the city of Kumasi, Ghana, Mayo Clinic and the City Cancer Challenge hosted a preceptorship program for comprehensive multidisciplinary breast and cervix cancer training. A total of 14 healthcare workers from Kumasi received two weeks of training at Mayo Clinic in November and December 2021. Each participant and preceptor were requested to complete an anonymous post-participation survey. Of the 14 trainee participants, 10 (71%) completed the survey. All respondents found the program “valuable and applicable to their clinical practice.” Ninety percent reported they were able to “review effective and critical elements in the development and expansion of the multidisciplinary team” and able to “solve practical clinical cases as a team”. General themes of satisfaction included: (1) organization and administration, (2) clinical observations and demonstrations, (3) guidelines development, and (4) recognizing the central importance of cultivating a team-based approach. Of the 40 preceptors, 16 (40%) completed the survey. All respondents reported they felt the training would meaningfully “influence patient care in Ghana”, that participation “added value or joy to their clinical practice,” and all wished to “participate in future preceptorship programs”. After a focused two-week program, trainees reported high satisfaction, usefulness from observing specialized cancer care, and value in closely observing a multidisciplinary oncology team. Preceptors reported the experience added joy and perspective to their clinical practice and wished to participate in future programs.

Evaluating climate change scenarios in the white volta basin: A statistical bias-correction approach - Jacob Kofi Mensah; Komlavi Akpoti; Eric Antwi-Ofosu; Amos T. Kabo-bah; Ebenezer K. Siabi; Austin Asare; Ransford W. Bakuri; Sandow Mark Yidana (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A modelling workflow for quantification of photobioreactor performance - Wenjia Gu; Emile Theau; Amos W. Anderson; David F. Fletcher; John M. Kavanagh; Dale D. McClure (Chemical Engineering Journal, 2023)

Atlantic ITCZ variability during the Holocene based on high-resolution speleothem isotope records from northern Venezuela - N. Melissa M. Medina; Francisco W. Cruz; Amos Winter; Haiwei Zhang; Angela Ampuero; Mathias Vuille; Víctor C. Mayta; Marília C. Campos; Verónica Marcela Rámirez; Giselle Utida; Andrés Camilo Zúñiga; Hai Cheng (Quaternary Science Reviews, 2023)

Free-living marine nematode communities in Rhizophora mucronata Lam. (Rhizophoraceae) forest at Mida Creek, Kenya - Beth W. Waweru; Agnes W.N. Muthumbi; Ann Vanreusel; Virginia Wangondu; Amos Mutua (Western Indian Ocean Journal of Marine Science, 2023)
Nematodes are among the most abundant organisms in marine ecosystems where they play a critical role in nutrient cycling, provision of nourishment to the higher organisms in the food web, pest control, and act as disease-causing vectors. This study determined the abundance and community structure of nematodes in three plots of Rhizophora mucronata forest stand at Kirepwe Macho and Dabaso sites at Mida Creek, Kenya. Replicated sediment samples were randomly collected from one forest plot in Kirepwe Macho and two plots in Dabaso during the months of January and April 2011. Total organic matter, sand and silt proportions were not significantly different across the study sites and between January and April. A total of 90 and 81 nematode genera were encountered in the month of January and April, respectively. At both sampling times, the nematode community was dominated by Terschellingia (20.5 % - 15.3 %) and Paracomesoma (10.6 % - 6.6 %). The Shannon-Weiner diversity index was relatively high in the three forest plots both in January and April ranging from 2.76 to 3.40. There was no significant difference in nematode community assemblage within sites (p > 0.05, 0.901) but there were differences between sampling time (p > 0.05, 0.001). The results showed that the three sites had similar nematode community structure suggesting that the three Rhizophora mucronata mangrove forest plots did not differ in terms of nematode generic composition even though the plots were not all close to each other.

Response to “Practice what you preach: Ensuring scientific spheres integrate Indigenous Peoples’ and Local Communities’ rights and agency too” by Lopez-Maldonado - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; David García-del-Amo; Natalia Hanazaki; Ana C. Luz; Pamela McElwee; Vicky J. Meretsky; Zsolt Molnár; Isabel Ruiz-Mallén; et al. (Ambio, 2022)

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

Full lifetime perspectives on the costs and benefits of lay‐date variation in tree swallows - David W. Winkler; Kelly K. Hallinger; Teresa M. Pegan; Conor C. Taff; Mo A. Verhoeven; David Chang van Oordt; Maria Stager; Jennifer J. Uehling; Maren N. Vitousek; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; et al. (Ecology, 2020)
Animals must balance various costs and benefits when deciding when to breed. The costs and benefits of breeding at different times have received much attention, but most studies have been limited to investigating short‐term season‐to‐season fitness effects. However, breeding early, versus late, in a season may influence lifetime fitness over many years, trading off in complex ways across the breeder’s lifespan. In this study, we examined the complete life histories of 867 female tree swallows ( Tachycineta bicolor ) breeding in Ithaca, New York, between 2002 and 2016. Earlier breeders outperformed later breeders in short‐term measures of reproductive output and offspring quality. Though there were weak indications that females paid long‐term future survival costs for breeding early, lifetime fledgling output was markedly higher overall in early‐breeding birds. Importantly, older females breeding later in the season did not experience compensating life history advantages that suggested an alternative equal‐fitness breeding strategy. Rather, most or all of the swallows appear to be breeding as early as they can, and differences in lay dates appear to be determined primarily by differences in individual quality or condition. Lay date had a significant repeatability across breeding attempts by the same female, and the first lay date of females fledged in our population was strongly influenced by the first lay date of their mothers, indicating the potential for ongoing selection on lay date. By examining performance over the entire lifespan of a large number of individuals, we were able to clarify the relationship between timing of breeding and fitness and gain new insight into the sources of variability in this important life history trait.

Influence of task-based airborne lead exposures on blood lead levels: a case study of informal automobile repair artisans in Nakuru town, Kenya - Owino Alfred Odongo; W. N. Moturi; Meshack Amos Obonyo (Environmental Geochemistry and Health, 2020)

Ethanol Exacerbates Manganese-Induced Neurobehavioral Deficits, Striatal Oxidative Stress, and Apoptosis Via Regulation of p53, Caspase-3, and Bax/Bcl-2 Ratio-Dependent Pathway - Kpobari W. Nkpaa; Ifeoluwa O. Awogbindin; Benjamin A. Amadi; Amos O. Abolaji; Isaac A. Adedara; Matthew O. Wegwu; Ebenezer O. Farombi (Biological Trace Element Research, 2019)

On the relationship between coral δ 13 C and Caribbean climate - Amos Winter; Mark Jury; Paul W. Sammarco; Davide Zanchettin (International Journal of Climatology, 2018)
A coral ( Orbicella faveolata ) δ 13 C isotope ratio record off the southwest coast of Puerto Rico is used to indicate regional ocean–atmosphere conditions over the 20th century. The coral δ 13 C record is correlated positively with North Atlantic sea surface temperature (SST) and local evaporation. Spatial correlation maps show a broad area of influence by SST, sea‐level pressure and evaporation to the northeast of Puerto Rico. The composite maps reflect a strengthening of the North Atlantic anticyclone and east Pacific counter‐currents during years of enhanced coral growth. The coral δ 13 C record presented here corresponds with a local cloud cover increase of ~10% in parallel with a 0.5 °C rise of local SST since 1900. Environmental conditions tend to lead coral growth in a knock‐on effect as seen in local SST, cloud cover and evaporation data. The coral community may thus be a sentinel of both multi‐year fluctuations and centennial trends in Central Caribbean climate.

The New Zealand gravimetric quasigeoid model 2017 that incorporates nationwide airborne gravimetry - J. C. McCubbine; M. J. Amos; F. C. Tontini; E. Smith; R. Winefied; V. Stagpoole; W. E. Featherstone (Journal of Geodesy, 2018)

Evaluation of the Regional Climate Model over the Loess Plateau of China - Lang Wang; Kevin K. W. Cheung; Chi‐Yung Tam; Amos P. K. Tai; Yubin Li (International Journal of Climatology, 2018)
This paper presents an evaluation study of the Regional Climate Model version 4.3 ( RegCM4 .3) over the Loess Plateau in northern China, which is a semi‐arid region characterized by complex topography. During recent years, a series of reforestation programmes have been implemented across the region that might influence the local climate in complex ways. To better understand the local climate, the RegCM4 .3 was applied to simulate the present‐day conditions over the Loess Plateau. The simulation was carried out from 1990 to 2009 at the 50‐km horizontal resolution, with lateral boundary conditions taken from the ECMWF ‐Interim reanalysis. A series of climate variables and processes were evaluated during the winter and summer seasons, such as 2‐m air temperature, precipitation, wind circulation, surface energy balance, full moisture budget, and cloud radiative forcing (CRF). The possible origins of the simulation bias and the physical linkages with other model processes were examined. In general, RegCM4 .3 is able to reproduce both the spatial and temporal features of the regional climate over the Loess Plateau. However, there are still biases in some meteorological variables including precipitation and 2‐m air temperature. In particular, the model tends to produce cold biases during winter and underestimate precipitation during summer. Further analyses indicates that the cold biases in winter may have resulted from the deficiency of the downward longwave radiation fluxes, excessive ground heat fluxes, and negative temperature advection by the seasonal mean circulation. These processes are primarily triggered by deficiencies in CRF and excessive northwesterlies over the plateau. The underestimated precipitation during summer is associated with a weak southerly monsoon in the model. A full moisture budget analysis reveals that the dry bias in this region can be mainly attributed to model deficiency in moisture advection and convergence, and to a lesser extent to that in surface evaporation.

Sedimentological interpretation of an Ediacaran delta: Bonney Sandstone, South Australia - J. W. Counts; F. Rarity; R. B. Ainsworth; K. J. Amos; T. Lane; S. Morón; J. Trainor; C. Valenti; R. Nanson (Australian Journal of Earth Sciences, 2016)

Comparative performance of mixed-sex and hormonal-sex-reversed Nile tilapia Oreochromis niloticus and hybrids (Oreochromis niloticus × Oreochromis urolepis hornorum) cultured in concrete tanks - Moses Mbiru; Samwel Mchele Limbu; Sebastian W. Chenyambuga; Hieromin Amon Lamtane; Rashid Tamatamah; Nazael Amos Madalla; Augustine Warioba Mwandya (Aquaculture International, 2016)

Protection by the flavonoids quercetin and luteolin against peroxide- or menadione-induced oxidative stress in MC3T3-E1 osteoblast cells - Amos A. Fatokun; Mercedes Tome; Robert A. Smith; L. Gail Darlington; Trevor W. Stone (Natural Product Research, 2015)

Global population structure and demographic history of the grey seal - A. Klimova; C. D. Phillips; K. Fietz; M. T. Olsen; J. Harwood; W. Amos; J. I. Hoffman (Molecular Ecology, 2014)
Although the grey seal Halichoerus grypus is one of the most familiar and intensively studied of all pinniped species, its global population structure remains to be elucidated. Little is also known about how the species as a whole may have historically responded to climate‐driven changes in habitat availability and anthropogenic exploitation. We therefore analysed samples from over 1500 individuals collected from 22 colonies spanning the Western and Eastern Atlantic and the Baltic Sea regions, represented by 350 bp of the mitochondrial hypervariable region and up to nine microsatellites. Strong population structure was observed at both types of marker, and highly asymmetrical patterns of gene flow were also inferred, with the Orkney Islands being identified as a source of emigrants to other areas in the Eastern Atlantic. The Baltic and Eastern Atlantic regions were estimated to have diverged a little over 10 000 years ago, consistent with the last proposed isolation of the Baltic Sea. Approximate Bayesian computation also identified genetic signals consistent with postglacial population expansion across much of the species range, suggesting that grey seals are highly responsive to changes in habitat availability.

Widespread amplification of amplified fragment length polymorphisms (AFLPs) in marine Antarctic animals - J. I. Hoffman; M. S. Clark; W. Amos; L. S. Peck (Polar Biology, 2012)

The mating system of the Mediterranean monk seal in the Western Sahara - T. Pastor; H. L. Cappozzo; E. Grau; W. Amos; A. Aguilar (Marine Mammal Science, 2011)
The mating system of the Mediterranean monk seal was studied combining the use of diverse technologies. Sexual dimorphism in size was limited. Sexual activity was only observed to occur in the water. The different segments of the population segregated spatially: females, pups, and juveniles aggregated inside two main caves, whose entrances were controlled by a small number (2–3) of territorial males that defended aquatic territories situated at the very mouth of the caves. Other territorial males defended aquatic territories located further away (5–30 km). The tenure of aquatic territories was nonseasonal and spanned several years. Relatedness among pups belonging to the same cohort was low or null, indicating a low level of polygyny, which is not surprising for an aquatically mating phocid with a protracted reproductive season. However, in addition, genetic relatedness showed a remarkable temporal periodicity. These results in combination point to the existence of a complex social structure in this species.

Phenotypic plasticity and genetic isolation-by-distance in the freshwater mussel Unio pictorum (Mollusca: Unionoida) - A. Zieritz; J. I. Hoffman; W. Amos; D. C. Aldridge (Evolutionary Ecology, 2010)

Health and lifestyle behaviors among persons at risk of Lynch syndrome - Allison M. Burton; Susan K. Peterson; Salma K. Marani; Sally W. Vernon; Christopher I. Amos; Marsha L. Frazier; Patrick M. Lynch; Ellen R. Gritz (Cancer Causes & Control, 2010)

Contrasting patterns of genetic diversity at three different genetic markers in a marine mammal metapopulation - J. I. HOFFMAN; K. K. DASMAHAPATRA; W. AMOS; C. D. PHILLIPS; T. S. GELATT; J. W. BICKHAM (Molecular Ecology, 2009)
Many studies use genetic markers to explore population structure and variability within species. However, only a minority use more than one type of marker and, despite increasing evidence of a link between heterozygosity and individual fitness, few ask whether diversity correlates with population trajectory. To address these issues, we analysed data from the Steller's sea lion, Eumetiopias jubatus , where three stocks are distributed over a vast geographical range and where both genetic samples and detailed demographic data have been collected from many diverse breeding colonies. To previously published mitochondrial DNA (mtDNA) and microsatellite data sets, we have added new data for amplified fragment length polymorphism (AFLP) markers, comprising 238 loci scored in 285 sea lions sampled from 23 natal rookeries. Genotypic diversity was low relative to most vertebrates, with only 37 loci (15.5%) being polymorphic. Moreover, contrasting geographical patterns of genetic diversity were found at the three markers, with Nei's gene diversity tending to be higher for AFLPs and microsatellites in rookeries of the western and Asian stocks, while the highest mtDNA values were found in the eastern stock. Overall, and despite strongly contrasting demographic histories, after applying phylogenetic correction we found little correlation between genetic diversity and either colony size or demography. In contrast, we were able to show a highly significant positive relationship between AFLP diversity and current population size across a range of pinniped species, even though equivalent analyses did not reveal significant trends for either microsatellites or mtDNA.

Taxonomic resolution, ecotypes and the biogeography of Prochlorococcus - Adam C. Martiny; Amos P. K. Tai; Daniele Veneziano; François Primeau; Sallie W. Chisholm (Environmental Microbiology, 2009)
Summary In order to expand our understanding of the diversity and biogeography of Prochlorococcus ribotypes, we PCR‐amplified, cloned and sequenced the 16S/23S rRNA ITS region from sites in the Atlantic and Pacific oceans. Ninety‐three per cent of the ITS sequences could be assigned to existing Prochlorococcus clades, although many novel subclades were detected. We assigned the sequences to operational taxonomic units using a graduated scale of sequence identity from 80% to 99.5% and correlated Prochlorococcus diversity with respect to environmental variables and dispersal time between the sites. Dispersal time was estimated using a global ocean circulation model. The significance of specific environmental variables was dependent on the degree of sequence identity used to define a taxon: light correlates with broad‐scale diversity (90% cut‐off), temperature with intermediate scale (95%) whereas no correlation with phosphate was observed. Community structure was correlated with dispersal time between sample sites only when taxa were defined using the finest sequence similarity cut‐off. Surprisingly, the concentration of nitrate, which cannot be used as N source by the Prochlorococcus strains in culture, explains some variation in community structure for some definitions of taxa. This study suggests that the spatial distribution of Prochlorococcus ecotypes is shaped by a hierarchy of environmental factors as well dispersal limitation.

Unification of New Zealand’s local vertical datums: iterative gravimetric quasigeoid computations - M. J. Amos; W. E. Featherstone (Journal of Geodesy, 2009)

Adenosine receptor ligands protect against a combination of apoptotic and necrotic cell death in cerebellar granule neurons - Amos A. Fatokun; Trevor W. Stone; Robert A. Smith (Experimental Brain Research, 2008)

Genetic tagging reveals extreme site fidelity in territorial male Antarctic fur seals Arctocephalus gazella - J. I. HOFFMAN; P. N. TRATHAN; W. AMOS (Molecular Ecology, 2006)
Genetic tagging, the identification of individuals using their genotypes, provides a powerful tool for studying animals that are difficult to observe or identify using conventional techniques. However, despite being widely adopted by conservation biologists, the full potential of this approach has yet to be realized. Here we used genetic recapture data to quantify male site fidelity at a colony of Antarctic fur seals where an aerial walkway provides unprecedented access and individual positions are determined daily to 1 m accuracy. Because males are too large and aggressive to be captured and fitted with conventional tags, we remotely collected 770 tissue samples over eight consecutive seasons and used nine‐locus microsatellite genotypes to reveal 306 genetic recaptures among 464 unique individuals. Within seasons, males are highly site‐faithful, with any movements that occur tending to take place before the period when females come into oestrus. Of those males that return to breed over successive seasons, almost half return to within a body length of where they were before. The discovery of such extreme site faithfulness has implications for the population structure and mating system of fur seals and potentially other colonially breeding species.

Dispersal, philopatry and intergroup relatedness: fine‐scale genetic structure in the white‐breasted thrasher, Ramphocinclus brachyurus - H. J. TEMPLE; J. I. HOFFMAN; W. AMOS (Molecular Ecology, 2006)
Dispersal is a fundamental process influencing evolution, social behaviour, and the long‐term persistence of populations. We use both observational and genetic data to investigate dispersal, kin‐clustering and intergroup relatedness in the white‐breasted thrasher, Ramphocinclus brachyurus , a cooperatively breeding bird that is globally endangered. Mark‐resighting data suggested sex‐biased dispersal, with females dispersing over greater distances while males remained philopatric. Accordingly, spatial autocorrelation analysis showed highly significant fine‐scale genetic structure among males, but not among females. This fine‐scale genetic structuring of the male population resulted in very high levels of relatedness between dominant males at neighbouring nests, similar to that seen within cooperative groups in many species where kin selection is cited as a cause of cooperation. By implication, between‐group as well as within‐group cooperation may be important, potentially creating a feedback loop in which short‐distance dispersal by males leads to the formation of male kin clusters that in turn facilitate nepotistic interactions and favour further local recruitment. The strength of spatial autocorrelation, as measured by the autocorrelation coefficient, r , was approximately two to three times greater than that reported in previous studies of animals. Relatively short dispersal distances by both males and females may have a negative impact on the white‐breasted thrasher's ability to colonize new areas, and may influence the long‐term persistence of isolated populations. This should be taken into account when designating protected areas or selecting sites for habitat restoration.

Coefficient of variation of sea surface temperature (SST) as an indicator of coral bleaching - Paul W. Sammarco; Amos Winter; J. Cody Stewart (Marine Biology, 2006)

Deep genetic subdivision within a continuously distributed and highly vagile marine mammal, the Steller's sea lion ( Eumetopias jubatus ) - J. I. HOFFMAN; C. W. MATSON; W. AMOS; T. R. LOUGHLIN; J. W. BICKHAM (Molecular Ecology, 2006)
The Steller's sea lion Eumetopias jubatus is an endangered marine mammal that has experienced dramatic population declines over much of its range during the past five decades. Studies using mitochondrial DNA (mtDNA) have shown that an apparently continuous population includes a strong division, yielding two discrete stocks, western and eastern. Based on a weaker split within the western stock, a third Asian stock has also been defined. While these findings indicate strong female philopatry, a recent study using nuclear microsatellite markers found little evidence of any genetic structure, implying extensive paternal gene flow. However, this result was at odds with mark–recapture data, and both sample sizes and genetic resolution were limited. To address these concerns, we increased analytical power by genotyping over 700 individuals from across the species’ range at 13 highly polymorphic microsatellite loci. We found a clear phylogenetic break between populations of the eastern stock and those of the western and Asian stocks. However, our data provide little support for the classification of a separate Asian stock. Our findings show that mtDNA structuring is not due simply to female philopatry, but instead reflects a genuine discontinuity within the range, with implications for both the phylogeography and conservation of this important marine mammal.

No relationship between microsatellite variation and neonatal fitness in Antarctic fur seals, Arctocephalus gazella - J. I. HOFFMAN; J. FORCADA; W. AMOS (Molecular Ecology, 2006)
Published studies of wild vertebrate populations have almost universally reported positive associations between genetic variation measured at microsatellite loci and fitness, creating the impression of ubiquity both in terms of the species and the traits involved. However, there is concern that this picture may be misleading because negative results frequently go unpublished. Here, we analyse the relationship between genotypic variation at nine highly variable microsatellite loci and neonatal fitness in 1070 Antarctic fur seal pups born at Bird Island, South Georgia. Despite our relatively large sample size, we find no significant association between three different measures of heterozygosity and two fitness traits, birth weight and survival. Furthermore, increasing genetic resolution by calculating parental relatedness also yields no association between genetic variation and fitness. Our findings are consistent with necropsy data showing that most pups die from starvation or trauma, conditions that are unlikely to be influenced strongly by genetic factors, particularly if the benefits of high heterozygosity are linked to immune‐related genes.

Mating system, philopatry and patterns of kinship in the cooperatively breeding subdesert mesite Monias benschi - N. SEDDON; W. AMOS; G. ADCOCK; P. JOHNSON; K. KRAAIJEVELD; F. J. L. KRAAIJEVELD‐SMIT; W. LEE; G. D. SENAPATHI; R. A. MULDER; J. A. TOBIAS (Molecular Ecology, 2005)
In the first molecular study of a member of the threatened avian family, Mesitornithidae, we used nine polymorphic microsatellite loci to elucidate parentage, patterns of within‐group kinship and occurrence of extra‐group paternity in the subdesert mesite Monias benschi , of southwest Madagascar. We found this cooperatively breeding species to have a very fluid mating system. There was evidence of genetic monogamy and polygynandry: of the nine groups with multiple offspring, six contained one breeding pair with unrelated helpers and three contained multiple male and female breeders with related helpers. Although patterns of within‐group kinship varied, there was a strong positive relationship between group size and relatedness, suggesting that groups form by natal philopatry. There was also a strong positive correlation between within‐sex and between‐sex relatedness, indicating that unlike most cooperatively breeding birds, philopatry involved both sexes. In contrast to predictions of kin selection and reproductive skew models, all monogamous groups contained unrelated individuals, while two of the three polygynandrous groups were families. Moreover, although between‐group variation in seasonal reproductive success was related to within‐group female relatedness, relatedness among males and between the sexes had no bearing on a group's reproductive output. While kin selection may underlie helping behaviour in females, factors such as direct long‐term fitness benefits of group living probably determine helping in males. Of the 14 offspring produced by fully sampled groups, at least two were sired by males from neighbouring groups: one by a breeding male and one by a nonbreeding male, suggesting that males may augment their reproductive success through extra‐group paternity.

Microsatellite genotyping errors: detection approaches, common sources and consequences for paternal exclusion - J. I. HOFFMAN; W. AMOS (Molecular Ecology, 2005)
Microsatellite genotyping errors will be present in all but the smallest data sets and have the potential to undermine the conclusions of most downstream analyses. Despite this, little rigorous effort has been made to quantify the size of the problem and to identify the commonest sources of error. Here, we use a large data set comprising almost 2000 Antarctic fur seals Arctocephalus gazella genotyped at nine hypervariable microsatellite loci to explore error detection methods, common sources of error and the consequences of errors on paternal exclusion. We found good concordance among a range of contrasting approaches to error‐rate estimation, our range being 0.0013 to 0.0074 per single locus PCR (polymerase chain reaction). The best approach probably involves blind repeat‐genotyping, but this is also the most labour‐intensive. We show that several other approaches are also effective at detecting errors, although the most convenient alternative, namely mother–offspring comparisons, yielded the lowest estimate of the error rate. In total, we found 75 errors, emphasizing their ubiquitous presence. The most common errors involved the misinterpretation of allele banding patterns ( n = 60, 80%) and of these, over a third ( n = 22, 36.7%) were due to confusion between homozygote and adjacent allele heterozygote genotypes. A specific test for whether a data set contains the expected number of adjacent allele heterozygotes could provide a useful tool with which workers can assess the likely size of the problem. Error rates are also positively correlated with both locus polymorphism and product size, again indicating aspects where extra effort at error reduction should be directed. Finally, we conducted simulations to explore the potential impact of genotyping errors on paternity exclusion. Error rates as low as 0.01 per allele resulted in a rate of false paternity exclusion exceeding 20%. Errors also led to reduced estimates of male reproductive skew and increases in the numbers of pups that matched more than one candidate male. Because even modest error rates can be strongly influential, we recommend that error rates should be routinely published and that researchers make an attempt to calculate how robust their analyses are to errors.

Does heterozygosity estimate inbreeding in real populations? - F. BALLOUX; W. AMOS; T. COULSON (Molecular Ecology, 2004)
Many recent studies report that individual heterozygosity at a handful of apparently neutral microsatellite markers is correlated with key components of fitness, with most studies invoking inbreeding depression as the likely underlying mechanism. The implicit assumption is that an individual's inbreeding coefficient can be estimated reliably using only 10 or so markers, but the validity of this assumption is unclear. Consequently, we have used individual‐based simulations to examine the conditions under which heterozygosity and inbreeding are likely to be correlated. Our results indicate that the parameter space in which this occurs is surprisingly narrow, requiring that inbreeding events are both frequent and severe, for example, through selfing, strong population structure and/or high levels of polygyny. Even then, the correlations are strong only when large numbers of loci (~200) can be deployed to estimate heterozygosity. With the handful of markers used in most studies, correlations only become likely under the most extreme scenario we looked at, namely 20 demes of 20 individuals coupled with strong polygyny. This finding is supported by the observation that heterozygosity is only weakly correlated among markers within an individual, even in a dataset comprising 400 markers typed in diverse human populations, some of which favour consanguineous marriages. If heterozygosity and inbreeding coefficient are generally uncorrelated, then heterozygosity–fitness correlations probably have little to do with inbreeding depression. Instead, one would need to invoke chance linkage between the markers used and one or more gene(s) experiencing balancing selection. Unfortunately, both explanations sit somewhat uncomfortably with current understanding. If inbreeding is the dominant mechanism, then our simulations indicate that consanguineous mating would have to be vastly more common than is predicted for most realistic populations. Conversely, if heterosis provides the answer, there need to be many more polymorphisms with major fitness effects and higher levels of linkage disequilibrium than are generally assumed.

Patterns of parental relatedness and pup survival in the grey seal (Halichoerus grypus) - K. BEAN; W. AMOS; P. P. POMEROY; S. D. TWISS; T. N. COULSON; I. L. BOYD (Molecular Ecology, 2004)
Levels of parental relatedness can affect offspring survival and susceptibility to disease. We investigated parental relatedness of live and dead Halichoerus grypus pups between and within island populations and between possible causes of mortality. Nine microsatellites were used to calculate internal relatedness (IR) and standardized mean d 2 . We find that pups with higher than average levels of IR have significantly lower survival and that this varied between island populations and that certain loci contributed to the effect more than others. Although, there were no significant differences between causes of mortality, peritonitis, infection and stillborn had the highest levels of IR. These results provide evidence that parental relatedness is an important determinant of pre‐weaning pup survival in the grey seal and that this may vary with cause of mortality given a larger sample size.

Combining demographic, environmental and genetic data to test hypotheses about colonization events in metapopulations - O. E. Gaggiotti; S. P. Brooks; W. Amos; J. Harwood (Molecular Ecology, 2004)
We describe a method for making inferences about the factors that influence colonization processes in natural populations. We consider the general situation where we have genetic data from a newly colonized population and also from I source populations that may have contributed individuals to the founding group that established the new population. The model assumes that p (biotic/abiotic) factors, G 1 , … , G p may have influenced some individuals in some of the source populations to find a new habitat patch where they could establish a new population. The aim of the method is to determine the composition of the founding group and to ascertain if the aforementioned factors have indeed played a role in the colonization event. We investigate the performance of our method using simulated data sets and illustrate its application with data from the grey seal Halichoerus grypus . These applications demonstrate that the method can identify accurately those factors that are most important for the founding of new populations. This is the case even when genetic differentiation among source populations is low. The estimates of the contribution that each source population makes to the founding groups is somewhat sensitive to the degree of genetic differentiation but it is still possible to identify the sources that are the main contributors to the founding group, even when genetic differentiation is low ( F ST = 0.01).

Population structure of long‐finned pilot whales in the North Atlantic: a correlation with sea surface temperature? - K. J. Fullard; G. Early; M. P. Heide‐Jørgensen; D. Bloch; A. Rosing‐Asvid; W. Amos (Molecular Ecology, 2000)
The long‐finned pilot whale, Globicephala melas , is a social, pelagic odontocete distributed widely in the cold temperate waters of the North Atlantic. Despite genetic, morphometric, physiological and observational studies, it remains unclear whether any population substructure exists. We have used eight highly polymorphic microsatellite loci to analyse samples from four disparate sampling sites: USA East Coast (Cape Cod), West Greenland, the Faeroe Islands and the UK. Our results indicate that substructure does exist, and is particularly pronounced between West Greenland and other sites. The magnitudes of the various pairwise comparisons do not support a simple isolation‐by‐distance model. Instead, the patterns of genetic differentiation suggest that population isolation occurs between areas of the ocean which differ in sea surface temperature. Such a mechanism is supported by the observation that temperature is a primary factor determining the relative distributions of two short‐finned pilot whale ( G. macrorhynchus ) populations off the Pacific coast of Japan.

Patterns of paternal relatedness in British grey seal colonies - J. Worthington Wilmer; A. J. Overall; P. P. Pomeroy; S. D. Twiss; W. Amos (Molecular Ecology, 2000)
Previous studies of breeding behaviour in the grey seal, Halichoerus grypus , have painted conflicting pictures. Behavioural observations suggest a classical polygynous system with a small number of dominant males fathering most of the offspring. However, genetic analysis suggests that many potential fathers spend little time ashore, that some pairs of seals show partner fidelity and that the dominant males are not as successful as their behaviour would suggest. Here we used paternal relatedness between pups with known mothers, sampled over an 11‐year period, to show that behavioural dominance leading to enhanced fitness is a feature of only a handful of males located near the centre of the breeding colony. The vast majority of pups are fathered by any of a large number of males who all share approximately equal success, including virtually all those males who have previously escaped our best sampling efforts. As expected, the frequency of full‐sibs is reduced in this longer time series relative to the original study. However, absolute estimates of the frequency of full‐sibs seem to be confounded by a tendency for females who produce paternally unrelated pups to have conceived to males who are more genetically dissimilar from each other than expected by chance alone. Together, these elements of breeding behaviour would help to maintain maximum genetic diversity and to minimize the effects of inbreeding.

Where have all the fathers gone? An extensive microsatellite analysis of paternity in the grey seal ( Halichoerus grypus ) - J. Worthington Wilmer; P. J. Allen; P. P. Pomeroy; S. D. Twiss; W. Amos (Molecular Ecology, 1999)
Microsatellites were used to conduct an extensive analysis of paternity of grey seals from two Scottish breeding colonies at North Rona ( n = 1189) and the Isle of May ( n = 694), spanning more than a decade. A maximum of 46% of pups at North Rona and 29% of pups at the Isle of May could be allocated a father, even though the majority of candidate males for specific study sites within each colony were believed to have been sampled. Based on the paternities which could be assigned, both colonies showed evidence of reproductive skew, apparently due to the presence of approximately five males who were exceptionally successful. Some males were assigned paternities at least 10 years before, and colleagues 10 years after, being sampled, implying a reproductive lifespan of at least 10 years, and there are indications that the real maximum lies in the range 15–20 years. Male grey seals appear to have at least two breeding strategies they can adopt. On land, some males benefit from a traditionally polygynous system. However, between 50 and 70% of grey seal pups born at a particular colony are not fathered by males who are likely to be sampled by us, implying that these males seldom venture ashore here. We conclude that aquatic mating may play a much larger role in the grey seal than has previously been thought.

Accessibility of T-tubule vacuoles to extracellular dextran and DNA: mechanism and potential application of vacuolation - Sergei A. Krolenko; W. Brad Amos; Susan C. Brown; Marina V. Tarunina; Jack A. Lucy (Journal of Muscle Research and Cell Motility, 1998)

GENETIC AND BEHAVIORAL EVIDENCE THAT HARBOR SEAL ( PHOCA VITULINA ) FEMALES MAY MATE WITH MULTIPLE MALES - E. A. Perry; W. Amos (Marine Mammal Science, 1998)

Distribution of phytoplankton and nutrients in relation to different water masses in the area around Elephant Island, Antarctica - O. Holm-Hansen; C. D. Hewes; V. E. Villafañe; E. W. Helbling; N. Silva; T. Amos (Polar Biology, 1997)

Molecular scatology: the use of molecular genetic analysis to assign species, sex and individual identity to seal faeces - J. Z. Reed; D. J. Tollit; P. M. Thompson; W. Amos (Molecular Ecology, 1997)
Seals and commercial fisheries are potential competitors for fish and cephalopods. Research into the diet of British seal species has been based on conventional dietary analyses, but these methods often do not allow assignment of species identity to scat samples. We present a protocol for obtaining DNA from seal scat (faecal) samples which can be used in polymerase chain reactions to amplify both nuclear and mitochondrial DNA. This can provide a method of identifying the species, sex and individual identity of the seal, from a particular scat sample. Combined with conventional dietary analyses these techniques will allow us to assess sources of variation in seal diet composition. Scat samples have been collected from intertidal haul‐out sites around the inner Moray Firth, north‐east Scotland. We have assessed methods to extract and purify faecal DNA, a combination of DNA from the individual seal, prey items, and gut bacteria, for use in PCR. Controls using faecal and blood samples from the same individual have enabled microsatellite primer sets from four pinniped species to be tested. Approximately 200 scat samples have been examined for species identity and individual matches. This study will provide essential information for the assessment of interactions between seals and commercial or recreational fisheries.

Long-chain fatty acids and ethanol affect the properties of membranes inDrosophila melanogaster larvae - Robert R. Miller; Amos O. Dare; Marcie L. Moore; Robert G. Kooser; Billy W. Geer (Biochemical Genetics, 1993)

Long-chain fatty acids and ethanol affect the properties of membranes inDrosophila melanogaster larvae - Robert R. Miller; Amos O. Dare; Marcie L. Moore; Robert G. Kooser; Billy W. Geer (Biochemical Genetics, 1993)

Effect of ?-cyclodextrin on mucochloric acid and 3-chloro-4-(dichloromethyl)-5-hydroxy-2(5H)-furanone - Ieva R. Politzer; Kathleen T. Crago; Wendy Benjamin; Jocelyn Joseph; Keith Amos; W. Emile Coleman (Archives of Environmental Contamination and Toxicology, 1991)